Dinar Dirham: Restoration of Shariah Currency Values for Indonesia Economic Prosperity - Alim, Sahirul; Fikriawan, Suad; Lubis, Ahmad Tarmizi; Nasri, Ulyan (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2024)
This study aims to investigate the restoration of Shariah currency values through the implementation of Dinar Dirham for fostering economic prosperity in Indonesia. Employing a mixed-method approach, the research combines qualitative and quantitative methodologies. Qualitative data is collected through literature review and expert interviews to understand the historical significance and contemporary relevance of Dinar Dirham in Islamic economics. Quantitative data is gathered through surveys and financial analysis to assess the potential impact of reintroducing Dinar Dirham on Indonesia's economic landscape. The collected data is analyzed using thematic analysis for qualitative data and statistical techniques for quantitative data. The research results indicate significant interest among stakeholders in reintroducing Dinar Dirham as a means to stabilize the economy and uphold Islamic principles in financial transactions. Qualitative data analysis reveals the strong historical and contemporary relevance of Dinar Dirham in Islamic economics, while quantitative data suggests the potential for increased economic stability through the reintroduction of this currency. The implications of this study suggest that reintroducing Dinar Dirham can enhance economic stability, promote ethical financial practices, and strengthen Indonesia's position in the global Islamic finance industry.